1986
DOI: 10.1002/1097-0142(19860515)57:10<1918::aid-cncr2820571005>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical trial using californium 252 fast neutron brachytherapy, external pelvic radiation, and extrafascial hysterectomy in the treatment of bulky, barrel-shaped stage IB cervical cancer

Abstract: From June 1977 to June 1983, 32 patients with bulky (greater than 4 cm diameter), barrel-shaped Stage IB cervical cancer were treated at the University of Kentucky Medical Center by a combination of outpatient neutron brachytherapy using californium 252 (252Cf) and external pelvic radiation followed by extrafascial hysterectomy. Nineteen patients had cervical tumors 4 to 6 cm in diameter, and 13 patients had lesions in excess of 6 cm in diameter. A dose of 4500 rad external photon therapy was given from a line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Cf-252 neutron source also has higher RBE and lower oxygen enhancement rate against photon radio-resistance. Cf-252 neutron ICBT has been found effective for radiotherapy and possesses radiobiological advantages in treatment of radio-resistant, advanced, or bulky cervical cancer [17,31]. In this regard, our current data support the effect of Cf-252 neutron ICBT combined with external beam radiotherapy on cervical AC and SCC.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Cf-252 neutron source also has higher RBE and lower oxygen enhancement rate against photon radio-resistance. Cf-252 neutron ICBT has been found effective for radiotherapy and possesses radiobiological advantages in treatment of radio-resistant, advanced, or bulky cervical cancer [17,31]. In this regard, our current data support the effect of Cf-252 neutron ICBT combined with external beam radiotherapy on cervical AC and SCC.…”
Section: Discussionsupporting
confidence: 72%
“…For example, a previous study reported by Maruyama and his associates [24] compared the effect of Cf-252 with Cs-173 ICBT combined with EBRT for stage III cervical cancer and showed 54 % 5-year OS rate with Cf-252 ICBT and 12 % with Cs-137 ICBT. After that, this group of physicians also conducted a phase II clinical trial [25] to compare the effectiveness of cf-252 ICBT and EBRT followed by extrafascial hysterectomy with Cs-137 ICBT on bulky and barrel-shaped stage IB cervical cancer. They found that 34 % (15/44) of patients were positive after Cs-137 and only one in 21 patients was positive after Cf-252 therapy.…”
Section: Discussionmentioning
confidence: 99%